Development of Interactive Story Tales Using MIT App Inventor - Jadán-Guerrero, Janio (2022)
Today mobile technologies have become essential in people’s lives. The use of smartphones and tablets has increased in times of pandemic due to their low cost, ease of use, ubiquity, portability, communication, and interactivity. Reading habits have changed significantly in favor of the digital format. This article describes a study to identify the way children from 8 to 12 years of age read on smartphones. The study was carried out in three phases: the first where an instrumented inquiry was carried out, collecting and analyzing data by applying a diagnostic test to 20 students; as well as a survey of 20 parents and 4 teachers in the language area. In the second stage, with the information collected, mobile educational resources were designed based on unpublished stories and activities focused on four language skills (reading, speaking, listening and writing). In a third stage, an intervention was carried out using the Thinking Aloud technique. The students were separated into two groups, 10 of them participated in a virtual session and 10 in a face-to-face session. In both cases, the results showed some reading habits as well as interest, motivation when there are interactive resources.